Disorders in the sensory processing and the learning of preschool and school children: Review of the literature - Sonia Esperanza Serna R.; Khrislie Katherine Torres L.; Mayra Alejandra Torres V. (Revista Chilena de Terapia Ocupacional, 2017)
Sensory processing disorder greatly affects people performance because it disturbs processes that allow them to interact with the surrounding world and coordinate their activity with it. Frequently, children with difficulties of this type are identified in the classroom, but there is not knowledge enough to understand what is happening to them, how to approach them and how to work interdisciplinary. For these reasons, this review aims to identify and analyse the outstanding conceptual elements in the literature and the characteristics of the empirical studies carried out in this discipline, which serve as a guide to those interested in the subject. For this purpose, an articles review published since 2005 to date was carried out, mainly in Spanish language. Among the consulted databases it can be found REDALYC, DOAJ, DIALNET, using as main descriptors: Sensory integration, learning, psychomotricity, disorder in the Sensory processing, sensory profile. It was contemplated texts describing some learning criteria affected by sensory processing deficiencies, explaining the Sensory Integration model and including alterations in sensory modulation processing and its affectation in occupational performance of the minors. Proving that the way each child processes the information obtained from the sensory systems is different and particular, considering that depends on several genetic, environmental and experiential factors, thus the deficits can have several causes